Plantar Pressure Changes with Use of an Intrepid Dynamic Exoskeletal Orthosis. Issue 1 (January 2020) - Stewart, Julianne; Djafar, Tatiana; Miltenberger, Richard; Kingsbury, Trevor; Wyatt, Marilynn
ABSTRACT: Introduction: Limb preservation procedures have become a much more common alternative to amputation after critical limb trauma, but high levels of disability result after both lower-limb amputation and lower-limb preservation. The Intrepid Dynamic Exoskeletal Orthosis (IDEO) is a custom passive-dynamic ankle-foot orthosis developed for use in military service members with critical lower-limb injuries. A proposed mechanism for pain reduction seen with the IDEO is decreased loading or pressure experienced during weight bearing. However, until this study, no actual plantar pressure data had confirmed this unloading during walking gait, and this proposed mechanism has not been examined. The aim of this study was to evaluate the effect of an IDEO on peak plantar pressure in the total foot as well as in each of the eight areas of the foot in a sample with foot and/or ankle injury. Methods: For this within-subjects study, 74 potential participants who had been prescribed a unilateral IDEO were identified from a retrospective review of a clinical registry of patients. Patients were then excluded if they had bilateral lower-limb injury, spine or pelvis injury, or central neurological disorder, yielding 42 subjects (40 males). Patients were aged 29.7 ± 8.1 years. For each patient, data collection was performed before initiating training in use of the IDEO. Pressure-sensitive insoles were used to collect plantar pressure data in both shod and IDEO conditions at self-selected walking speeds. These trials were performed in a flat, linear hallway without turns or obstacles. The foot was divided into eight regions for analysis: medial and lateral sections of the hindfoot, midfoot, and forefoot, and greater and lesser toes. Results: Peak pressures were significantly decreased in the affected foot with use of the IDEO with up to 64% decreases seen at the forefoot and toes. Increases in peak pressure of up to 24% were seen in some regions of the unaffected foot as well as the total foot. Discussion: These findings help provide insight into the mechanism behind the improvement in function and decrease in pain that has been seen with use of the IDEO. The slight increases in plantar pressure seen in the unaffected foot with use of the IDEO may be due to higher gait velocity in the IDEO condition than in the shod condition (1.26 ± 0.14 m/s IDEO vs. 1.19 ± 0.17 m/s shod). Gait velocity was collected using instrumented gait analysis performed immediately before plantar pressure data collection. Alternately, overloading of the sound limb may be occurring due to unfamiliarity with the IDEO. Conclusions: Despite a growing body of evidence for functional improvements with use of the IDEO, this is the first study to confirm that this brace can decrease peak plantar pressure, particularly in the forefoot and toes of the affected foot, during walking. This outcome provides insight to clinicians seeking a device to improve painful gait, particularly for conditions of the foot or ankle that produce pain in weight bearing. In addition, although the IDEO was designed to enable performance of high-level activities in a population with critical limb injury, this study provides support for using the IDEO for walking by those with a diverse collection of injuries.